'Cultural life', disability, inclusion and citizenship moving beyond leisure in isolation - Darcy, Simon, 1964-; Singleton, Jerome F., 1950- (Routledge,Taylor & Francis Group, 2015)
Disability is a complex multidimensional social construct where the type of disability and the level of support of individuals needs to be considered within leisure provision. In a leisure context, people with a disability often face a multitude of constraints to participation. However, when leisure is possible, the benefits are substantial and worth pursuing. While other marginalised populations have received a great deal of attention across disciplines and in the field of leisure and recreation, disability has received comparatively less attention and generally in isolation to the leisure context. This book concentrates on "disability citizenship in leisure". The chapters focus on examining the leisure lives of people with different types of disability by supporting their leisure endeavours through innovations in technology, service provision and the imagination. Each chapter has a different social setting, involves different groups of people with disability, and challenges conventional wisdom about what is possible when ability is seen, nurtured and, then, flourishing with the opportunities provided. Rather than leisure being seen in isolation, the context of this book explores leisure as part of everyday lives of people with disabilities whether that be part of promoting inclusive practices across University basis, invoking an innovative technology of Photovoice to allow people with intellectual disability to provide insight into their hopes and dreams of community living, maintaining mental health in refugees through innovative leadership programs or how people with traumatic brain injury can regain autonomy through the arts. We situate the book in the context of further challenging researchers to think beyond disability as a context in their research and engagement of the person as a citizen in leisure opportunities, as opposed to a disability.